PERHITUNGAN HUJAN EFEKTIF DENGAN METODE SCS-CN DAN PENGARUHNYA TERHADAP HIDROGRAF SATUAN - Anggi Nidya Sari; Joko Sujono; Rachmad Jayadi (Inersia: Jurnal Teknik Sipil, 2019)
The change of landuse at watershed (DAS) could influence that watershed’s condition. This affects runoff condition or changed of discharge of watershed. Lack of attention toward water resource management causes low support capacity of DAS such as lack of infiltration capacity or lack of water storage capacity. The understanding about process and how much effective rainfall happens including influencing factors are very needed as model to apply watermanagement and use system of field more effective. This research was conducted in five DAS of DI Yogyakarta and DAS in Central Java area. Those five DAS were DAS Code in Pogung, Code in Kaloran, Gajahwong in Papringan, Bogowonto in Pungangan and Progo in Badran. Effective rainfall method can be analysis by SCS-CN method. Effective rainfall obtained from  these methods would be used for unit measurement of flood discharge design with unit hydrograph method.The result of research showed that The value of effective rainfall varied well from SCS-CN method. The design for flood discharge measurement with unit hydrograph method to compared with analysis frequency method. Initial abstraction is also very influential in the SCS-CN method.